Efecto de la implementación del sello de agricultura familiar campesina AFC. En las familias campesinas de la parroquia Toacaso, como estrategia de integración en el proceso de comercialización de productos agropecuarios . - Barbosa Reyes, José Miguel (2020)
With the completion of this degree project, the aim is to evaluate the effect on the implementation of the peasant family agriculture seal developed by the MAG, as an integration strategy in the process of commercialization of agricultural products in the Toacaso parish of the Latacunga canton, Cotopaxi province. In order to identify, investigate and analyze the proposed goals, a bibliographic review was carried out on peasant family agriculture in Latin America and the Caribbean "FAO - MERCOSUR" as well as the different peasant labels in South America, said information was used to characterize producers - consumers. Interviews were conducted as an object of study to the Entrepreneurs Association of Cotopaxi with 15 active partners as heads of household, who had problems in the marketing (supply - demand) of their products before obtaining the AFC seal, which through the MAG Cotopaxi were beneficiaries of the AFC card, which allowed them to get involved in different alternative CIALCOS marketing circuits (citizen fairs, direct supply to industry or companies, food baskets, supply to hotels, restaurants and HORECAS coffee shops) at the level of the province and the country strengthening the food sovereignty of Ecuador, supplying quality agroecological products. The producers are satisfied as well as the consumers pointed out that the Seal should not be granted to all the producers since it must certify the social origin and value the peasant producer with his clean production and promote socioeconomic development as well as family well-being avoiding the migratory development of the members of the family.